2016
DOI: 10.4103/0975-1475.186367
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination by mandibular ramus: A digital orthopantomographic study

Abstract: Aims and Objectives:(1) To determine the usefulness of mandibular ramus as an aid in sex determination. (2) To evaluate Anteroposterior | superioinferior angle of mandibular condyle.Materials and Methods:A retrospective study was conducted using orthopantomographs of 60 males and 60 females, which were taken using Kodak 8000C Digital Panoramic and Cephalometric System (73 kVp, 12 mA, 13.9 s). The age group ranged between 18 – 45 years. Mandibular ramus measurements were carried out using Master View 3.0 softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
3
16
0
3
Order By: Relevance
“…According to Samantha et al, 14 similar results were seen in corrsepondance to the present study where the condylar height was found to be significant and the mean values for males is 65.34mm and in females it was 61.69mm and the coronoid height plays no significant role which was in correlation with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to Samantha et al, 14 similar results were seen in corrsepondance to the present study where the condylar height was found to be significant and the mean values for males is 65.34mm and in females it was 61.69mm and the coronoid height plays no significant role which was in correlation with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were noticed in a study done by Sairam et al, 13 comparing the different mandibular measurements, the condylar height was found to be significant in gender determination with mean in males and females being 65.01mm and 59.48mm on right side and 65.71mm and 59.65mm on left side. According to Samantha et al, 14 similar results were seen in corrsepondance to the present study where the condylar height was found to be significant and the mean values for males is 65.34mm and in females it was 61.69mm. In a study done by Saraswathi G et al, 15 using CBCT images of 50 males and 50 females with a mean condylar height in males was 65.79mm and in females was 61.80mm thus concluded that the height of the condyle can be the best parameter.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, the greatest sexual dimorphism was at the maximum ramus height [27] in accordance with the results of Schultze et al, [12] and Kambylafkas et al, [28] which assured that mandibular ramus showed differences between the sexes more than mandibular body. Similar results were reported by Samatha et al, [29] as the projective height of ramus showed the highest sexual dimorphism and least was seen with minimum ramus breadth. Projective height of ramus, maximum ramus breadth and condylar height was statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…1,2 Thus, the part of skull such as mandible can have high diagnostic value. 5 The mandible itself is a large and very strong bone from the skull, therefore it is used for analysis. Basically, men bones are bigger and strong than women, because the shape, strength and angulation of the masticatory muscles affect the expression of mandibular dimorphism, because the degree of use of these muscles varies in men and women.…”
Section: Introductionmentioning
confidence: 99%